Overexpression of PRR11 promotes tumorigenic capability and is associated with progression in esophageal squamous cell carcinoma - Zhou, Li (Onco Targets Ther, 2019)
INTRODUCTION: Esophageal squamous cell carcinoma (ESCC) is one of the most common malignancies of gastrointestinal tract in the world, and the long-term prognosis for ESCC patients still remains dismal due to the lack of effective early diagnosis biomarkers. MATERIALS AND METHODS: Western blot and immunochemistry were used to determine the expression of PRR11 in 201 clinicopathologically characterized ESCC specimens. The effects of PRR11 on stem cell-like traits and tumorigenicity were examined by tumor sphere formation assay and SP assays in vitro and by a tumorigenesis model in vivo. The mechanism by which PRR11 mediated Wnt/β-catenin signaling was explored using luciferase reporter, immuno-chemistry, and real time-PCR (RT-PCR) assays. RESULTS: We found that PRR11 was markedly upregulated, at the level of both transcription and translation, in ESCC cell lines as compared with normal esophageal epithelial cells (NECCs). Immunohistochemical analysis showed that 69.2% paraffin-embedded archival ESCC specimens exhibited high levels of PRR11 expression, and multivariate analysis revealed that PRR11 upregulation might be an independent prognostic indicator for the survival of patients with ESCC. Furthermore, overexpression of PRR11 dramatically enhanced, whereas inhibition of PRR11 reduced the capability of cancer stem cell (CSC)-like phenotypes and tumorigenicity of ESCC cells both in vitro and in vivo. Mechanically, we demonstrated PRR11-enhanced tumorigenicity of ESCC cells via activating Wnt/β-catenin signaling, and PRR11 expression is found to be significantly correlated with β-catenin nuclear location in ESCC. CONCLUSION: Our findings suggest that the PRR11 might represent a novel and valuable prognostic marker for ESCC progression and play a role during the development and progression of this malignancy.